Kerja Sama Antar Daerah untuk Meningkatkan Pembangunan Daerah dan Pelayanan Publik di Kabupaten Sidoarjo dan Kota Surabaya - Devi Yulisya; Aldi Nugroho; Putri Nur Avia; Galih Wahyu Pradana (BISMA : Business and Management Journal, 2025)
This research examines the implementation of cooperation between Surabaya City Government and Sidoarjo Regency Government in order to improve regional development and public services in border areas. The focus of this research is to analyze the implementation of development cooperation and public services based on seven main principles: transparency, accountability, participation, efficiency, effectiveness, consensus, and mutual benefit and respect. The research method used is qualitative research with a literature study approach, with the results showing that this cooperation is able to optimize human, financial and infrastructure resources so that integrated infrastructure development and public administration services can run synergistically. The cooperation also successfully facilitated knowledge transfer and institutional capacity building. However, challenges such as differences in local regulations, political interests, and budget limitations are obstacles that must be overcome through continuous evaluation and coordination.